Permian trilobites and the applicability of the “living fossil” concept to extinct clades - Hopkins, Melanie J.; Wagner, Peter J.; Jordan, Katherine J. (Frontiers in Ecology and Evolution, 2023)
Some taxa occupy our imaginations as “living fossils” because they were known from the fossil record before being discovered alive today. Other taxa are considered “living fossils” because modern relatives bear a strong morphological resemblance to fossil relatives, or because they occupy a contracted geographic range or have less diversity now than in the past, or because they represent phylogenetic diversity that requires conservation. A characterizing feature of living fossils-–and thus an implicit assumption of all criteria--is that the “living fossil” of interest is extant. However, the general research questions that “living fossils” inspire--Why do rates of evolution vary across organisms, across traits, and across time? Why do some clades decline in diversity over extended periods?--may be applied to any clade, including completely extinct clades. We propose that there is nothing special about “now” when it comes to pursuing these questions and that it is unnecessarily limiting to restrict research programs to clades for which an extant member meets some conception of the “living fossil” moniker. To this end, we investigate the extent to which Permian trilobites might resemble “living fossils”, albeit from the perspective of 253 million years ago, when the last trilobites were still alive. We do so by comparing the taxonomic diversity, geographic range, and morphological disparity of trilobites living in the Permian to earlier time periods. We find that Permian trilobites meet most definitions of living fossils, although our assessment of morphological change and character retention depend on taxonomic scale.